Desain rumah minimalis pilihan type 36-100 : plus RAB (Rencana Anggaran Biaya) / Anditya, Muhammad Aulia Rahim ; penyunting, Erick - ANDITYA; Muhammad Aulia Rahim (Citra Media Pustaka, 2014)
114 hlm. : ilus. ; 26 cm.